Highly active antiretroviral therapy increases fibrinolytic and protein activity in pregnant women - Osime, Evarista Odaburhine; Obar, Catherine (Faculty of Medicine, Trisakti University, 2018)
BACKGROUNDVarious studies have examined optimal methods for Prevention of Mother to Child Transmission (PMTCT) of human immunodeficiency virus (HIV) and subsequent outcome of response to highly active antiretroviral therapy (HAART) as well as the impact of pregnancy on outcomes of HIV in the Pre-HAART era. Little is known of the impact of pregnancy in response to HAART in Africa. This study is aimed to evaluate euglobulin lysis time (ELT), protein C and protein S in HIV-positive pregnant women on HAART.Â METHODSThis was a cross-sectional study comprised of 150 participants attending Ante-Natal Clinic (ANC) in Central Hospital, Benin City. Pregnant women on HAART (Test subjects) (n=50, mean age 34 years), 50 pregnant newly diagnosed HIV-positive women that had not yet commenced HAART (n=50, mean age 31 years) and 50 pregnant HIV-negative women (n=50, mean age 30 years) which served as controls. The ELT was determined by methods described by Bain, protein C and protein S were determined using Enzyme Linked Immunosorbent Assay (ELISA).Â RESULTSThere was a significant increase in ELT in both pregnant women on HAART and not on HAART) when compared to HIV-negative pregnant women (p<0.05). There was a significant decrease in protein C in test subjects when compared with controls (p<0.05) and protein S increased significantly in HIV-positive pregnant women on HAART when compared to those not on HAART and HIV-negative pregnant women (p<0.05). Â CONCLUSIONThere are changes in ELT, protein C and protein S parameters with the introduction of HAART in pregnancy.